Colon Transcriptomics Reveals Sex-Dependent Metabolic Signatures in Response to 2-Amino-1-methyl-6-phenylimidazo[4,5-b]pyridine Treatment in C57BL/6N Mice - Pan, Jeong Hoon (Int J Mol Sci, 2020)
Diets high in red meats, particularly meats cooked at high temperature, increase the risk of colon cancer due to a production of heterocyclic aromatic amines (HAAs). Of the identified HAAs, 2-amino-1-methyl-6-phenylimidazo[4,5-b]pyridine (PhIP) is the most mass abundant colon carcinogen in charred meat or fish. Here, we comprehensively examined sex-dependent colon transcriptome signatures in response to PhIP treatment to identify biological discrepancies. Eight-week-old male and female C57BL/6N mice were intraperitoneally injected with PhIP (10 mg/kg of body weight) and colon tissues were harvested 24 h after PhIP injection, followed by colon transcriptomics analysis. A list of differentially expressed genes (DEGs) was utilized for computational bioinformatic analyses. Specifically, overrepresentation test using the Protein Analysis Through Evolutionary Relationships tool was carried out to annotate sex-dependent changes in transcriptome signatures after PhIP treatment. Additionally, the most significantly affected canonical pathways by PhIP treatment were predicted using the Ingenuity Pathway Analysis. As results, male and female mice presented different metabolic signatures in the colon transcriptome. In the male mice, oxidative phosphorylation in the mitochondrial respiratory chain was the pathway impacted the most; this might be due to a shortage of ATP for DNA repair. On the other hand, the female mice showed concurrent activation of lipolysis and adipogenesis. The present study provides the foundational information for future studies of PhIP effects on underlying sex-dependent mechanisms.